Studies on the physiology and biochemistry of internal disorders in plums (Prunus salicina cv. Songold) with special reference to gel breakdown - Taylor, M. A.(Martin Anthony) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1993.